M&M wheels: a fun learning tool for nomenclature and classification of amines / Gan Fie Chuen, Azlaini Mohamed Sally and Norul Safarinie Abdullah - Chuen, Gan Fie; Mohamed Sally, Azlaini; Abdullah, Norul Safarinie (2020)
This study involved 18 students from a practicum group (S1FP3) in Negeri Sembilan Matriculation College. A pre-test and brief interviews found these students encountered difficulties in classifying, naming and drawing the structures of primary, secondary and tertiary (1o, 2o, 3o) amines. They also failed to differentiate between the aliphatic and aromatic amines. Therefore, an innovative learning tool known as M&M (Mix and Match) Wheels was developed by “Chem Riders” to address the above problems. Using M&M Wheels, students were able to engage in small group activities involving constructing and naming various structures of 1o, 2o and 3 amines. M&M Wheels also utilized QR codes that are linked to examples of 1o, 2o and 3 aliphatic and aromatic amines for students’ reference. A post- test was conducted to evaluate students’ achievement after using M&M Wheels. Data analysis showed a significant improvement in students’ score for the post-test (mean score = 9.78) compared to pre-test (mean score = 6.56). Students also showed positive views towards the usage of the learning tool in M&M Wheels Questionnaire. In conclusion, this study found that M&M Wheels facilitated learning in a fun, interactive and meaningful way besides serving as a tool for developing students’ social skills. It is also an effective formative assessment tool for learning “Nomenclature and Classifications of Amines”.